2001
DOI: 10.1109/77.920101
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic interaction force between high-Tc superconductor-ring and magnet

Abstract: 1665 0.5 0.4 0.3 h z 0.2 W 0 0.1 t Y 2 0.0 -0.1Abstract-The magnetic interaction force between a superconducting ring and cylindrical permanent magnets of different lengths, aligned coaxially, has been investigated experimentally at zero-field-cooled and field-cooled conditions. The force as a function of the position of the magnet relative to the superconductor ring is qualitatively that expected if the superconductor is regarded as a diamagnet with non-ohmic dissipation. The hysteretic behavior of the axial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The axial force is enhanced with respect to the axially centered case (x = 0,y = 0). This behaviour is similar to that found experimentally by Ma et al [9]. Although Ma et al located nominally the magnet at the z-axis-corresponding to our Fig.…”
Section: Axially Oriented Dipolesupporting
confidence: 90%
See 1 more Smart Citation
“…The axial force is enhanced with respect to the axially centered case (x = 0,y = 0). This behaviour is similar to that found experimentally by Ma et al [9]. Although Ma et al located nominally the magnet at the z-axis-corresponding to our Fig.…”
Section: Axially Oriented Dipolesupporting
confidence: 90%
“…A non-ferromagnetic rotor may be attached axially to the magnet while the superconducting ring constitutes the stator. Axial forces between a superconducting ring and a magnet aligned to and located at its axis were measured by Ma, Postrekhin Ye and Chu in 2001 [9] . They found a maximum for the magnet at the border of the ring, a minimum for the magnet at the center of the ring and oscillations of the force with the axial position.…”
Section: Introductionmentioning
confidence: 99%
“…Questions on the inconsistency between the Meissner effect and Lenz's law or whether superconductors abide by Lenz's law have sometimes been raised [9][10][11][12][13], but there has as yet been no well-agreed explicit answer. Studies on the interaction between a magnet and a superconducting ring have mainly focused on the properties of a journal bearing constructed with a magnet and a high-temperature superconductor (HTS) bulk or ring [14][15][16], the outcomes from which are never able to answer the above question.…”
Section: Introductionmentioning
confidence: 99%
“…This system was subject to many theoretical and experimental investigations within the last few years which makes it of special interest. Ma et al [4], studied experimentally the levitation force between superconducting ring and cylindrical magnet. They concluded that the ring shaped SC/PM system is an attractive candidate for low loss magnetic bearing.…”
mentioning
confidence: 99%